Prescription of topiramate to treat alcohol use disorders in the Veterans Health Administration - Del Re, A C (BioMed Central, 2013)
BACKGROUND: As a quality improvement metric, the US Veterans Health Administration (VHA) monitors the proportion of patients with alcohol use disorders (AUD) who receive FDA approved medications for alcohol dependence (naltrexone, acamprosate, and disulfiram). Evidence supporting the off-label use of the antiepileptic medication topiramate to treat alcohol dependence may be as strong as these approved medications. However, little is known about the extent to which topiramate is used in clinical practice. The goal of this study was to describe and examine the overall use, facility-level variation in use, and patient -level predictors of topiramate prescription for patients with AUD in the VHA. METHODS: Using national VHA administrative data in a retrospective cohort study, we examined time trends in topiramate use from fiscal years (FY) 2009–2012, and predictors of topiramate prescription in 375,777 patients identified with AUD (ICD-9-CM codes 303.9x or 305.0x) treated in 141 VHA facilities in FY 2011. RESULTS: Among VHA patients with AUD, rates of topiramate prescription have increased from 0.99% in FY 2009 to 1.95% in FY 2012, although substantial variation across facilities exists. Predictors of topiramate prescription were female sex, young age, alcohol dependence diagnoses, engagement in both mental health and addiction specialty care, and psychiatric comorbidity. CONCLUSIONS: Veterans Health Administration facilities are monitored regarding the extent to which patients with AUD are receiving FDA-approved pharmacotherapy. Not including topiramate in the metric, which is prescribed more often than acamprosate and disulfiram combined, may underestimate the extent to which VHA patients at specific facilities and overall are receiving pharmacotherapy for AUD.